ANALISIS KELAYAKAN USAHA PADA D’LEFANICA BAKERY DI KOTA AMBON: PERSPEKTIF KEUANGAN, PEMASARAN, DAN MANAJEMEN - Rintan Dwi Saputri; Christina Sososutiksno; Pranatalindo Simanjuntak; Putri Dewi Nur Asis; Rosaria Anjali Rettobjaan; Rahmadani Bugis; Vivin Wance; Giofany Monik Luhukay (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This study aims to conduct a comprehensive feasibility analysis of D'Lefanica Bakery from three main perspectives, namely finance, marketing, and management. The method used is an applied method with a descriptive data approach. The results of the analysis show that D'Lefanica Bakery is financially feasible because it has a positive NPV, a Net B/C value well above 1, initial investment capital that can be recovered within a period of 1 year, and a very high IRR. Based on the marketing aspect, this business is considered quite effective because it has successfully implemented a marketing mix (4Ps). However, the main limitation lies in the promotion of the business, which still relies on word of mouth and social interaction. In terms of management, although D'Lefanica Bakery relies on a single chef, it has been able to implement a simple line organizational structure and principles of professionalism in its daily managerial activities.